The Influence Sequence Picture on Indonesian ELT Learners Writing Skill - Amiruddin; Inayah, Nur; Adzim, Syahrun; Mayasari, Andi; Aulinnia, Via (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The goal of this study was to see if using sequence graphics when writing procedural text improves writing skills. As a result, a quasi-experimental approach was used in this study. In both the pre-test and post-test, data on the students' writing abilities were gathered using the interview method. After gathering the data, descriptive analysis was used to examine it. The study included 13 students from IAI As'adiyah Sengkang, Indonesia, who were in their fifth semester of English education. Cluster random sampling was used to gather them. To measure the progress of the sequence picture technique, the researcher conducted a t-test study. The study findings revealed that there was no statistically significant difference between the pretest and posttest. The t-test value (0.11) was found to be greater than the level of significance α (0.05) and degree of freedom (df) = 41. The researcher finds that employing the sequence pictures technique does not significantly improve students' writing skills in procedural text based on the findings and discussion of the study.